Inclusivity and Decentralisation: Women Legislative Candidacy from the Partai Demokrasi Indonesia Perjuangan in Manado City - Jovano Deivid Oleyver Palenewen; Katerina Bataha; Gloria Regina Rumimpunu (Universitas Syiah Kuala and Collaboration Yayasan Yusda Edu Indonesia, 2026)
In general, studies on women's political representation in political parties tend to highlight issues In general, studies on women's political representation in political parties tend to highlight issues such as low quotas, gender bias, or a lack of structural support for female candidates. This perspective often positions women as victims of a masculine and hierarchical system, without sufficiently revealing the internal mechanisms of parties that actually open up space for women's active and strategic participation. This study examines the political candidacy process for women in the PDI-P. The success of PDI-P in Manado City in the 2024 elections, with a 40% quota for women as legislative candidates, has drawn attention to how candidate selection is conducted within the party. This research focuses on two main dimensions: inclusivity and decentralization in candidate selection. Although women's representation in the list of legislative candidates has formally reached or exceeded the 30% quota, few studies have highlighted how this selection process unfolds internally within the party's local structures. The internal institutional configuration of the party allows for the nomination of women not merely as an administrative obligation but as part of political strategy and cadre development. Data were collected through in-depth interviews, participant observations, and analysis of official documents, and then analyzed qualitatively. This finding is important; it shows that real gender inclusion happens not just through quotas, but through internal party practices—especially ideology, local empowerment, and structured cadre development. These are key lessons for how parties can move beyond symbolic representation.